Factors associated with HIV positive pregnant women's participation in prevention of mother to child transmission of HIV programme at Thyolo District Hospital, Malawi - Chanachi, Serra (2021)
The Prevention of Mother to Child Transmission (PMTCT) of HIV program aims at reducing transmission of HIV infection from mother to child. The problem worldwide is that very few HIV positive (HIV+) pregnant women utilize PMTCT of HIV services. The purpose of this study was to identify factors that influence HIV+ pregnant women’s participation in PMTCT of HIV program at Thyolo District Hospital, Malawi. This was a quantitative descriptive research study conducted at Thyolo District Hospital. A total of 106 HIV+ pregnant women, attending antenatal care services participated in this study. A convenient purposive sampling was used to select the study respondents and a structured questionnaire with 46 questions was used to collect data from the respondents. The data was analyzed by the computer package called Statistical Package for Social Science, (SPSS) version 16.0 windows. Results of this study showed that knowledge on Mother to Child Transmission (MTCT) and PMTCT of HIV among HIV+ pregnant women was very high and this significantly influenced utilization of PMTCT services. Among the respondents, 99.1% (n = 105) heard about MTCT and were able to mention the period of time when the virus can be transmitted from an infected mother to the baby. The most frequently mentioned period was during delivery (83 %, n = 88) followed by during breastfeeding (77.4%, n = 82) and during pregnancy (54.7%, n = 58). However, 1.9 %, n = 2 of the respondents did not know any way of how an HIV + pregnant woman can transmit the virus to her baby to her baby. In addition, 87.7 % (n = 93) of the respondents heard about PMTCT of HIV. All the study respondents (100%) were able to identify at least one way of PMTCT of HIV. Most frequently mentioned way was through practicing exclusive breast feeding (46.2%, n = 49) followed by having safe delivery at hospital (44.3%, n = 47). However, 9.4 %, n = 10 of the respondents did not know any way of PMTCT. Other significant factors noted to influence the utilization of PMTCT services were educational level and knowledge of own HIV status before pregnancy. Most of the study respondents (78.3%, n = 83) had some education and (57.5 %, n = 61) had knowledge of their HIV status before they became pregnant and starting antenatal care. Some of the factors noted to hinder participation included distance to the PMTCT of HIV clinic and stigma and discrimination on HIV in the community. Most of the respondents (73.9%, n = 78), reported taking one to four hours to get to the clinic. This study found that stigma and discrimination against HIV and AIDS exists in Thyolo district because 1.1 % (n = 1) of the respondents were abandoned after disclosure of HIV + results to their spouses. The study recommends that MOH should embark on IEC campaigns to improve knowledge on MTCT and PMTCT in the community and men should actively be involved. Additionally, there should be community based education and sensitization regarding HIV and AIDS, and specific education against stigma and discrimination. Furthermore, this study recommends that MOH should increase access to HTC services to all women of reproductive age so that they should know their status before they become pregnant. Additionally, referral from HTCT clinics to family planning, and PMTCT of HIV program should be strengthened. This study also recommends that MOH should also ensure an adequate number of health workers including support staff who are also trained in PMTCT of HIV in all PMTCT sites. All PMTCT staff should be supportive, and should take great care to ensure confidentiality and privacy. The study recommends that individual and couple counseling should be stressed in all PMTCT of HIV clinics. All clients should be treated as individuals and more time should be set aside for counseling each client for them to make informed decisions. All PMTCT staff should have good attitude, be supportive and should take great care to ensure confidentiality and privacy. This will also ensure that adequate information is passed to all clients. Evidence by several researchers has shown that HIV+ pregnant women fail to participate in PMTCT services because of bad attitudes of health workers (Varga, 2008), fear of their status being disclosed to other people, and fear of being discriminated by health workers, family and community members Kasenga, Hurtig, and Emmelin (2008); andNjunga (2008). This study recommends that PMTCT of HIV should be incorporated in pre-service education curriculum and should also be part of topics taught during in-service education. This will ensure that all nurse/midwives are knowledgeable on PMTCT and able to offer the service at all levels. Furthermore, this study recommends that more studies should be conducted in the area of PMTCT of HIV. These studies may be such as adherent to PMTCT program and experiences of HIV + pregnant women who go through PMTCT program. All participants in this study were participating in PMTCT program but we don’t know if they were able to adhere to the program protocols.